Pengukuran Tingkat Kesejahteraan Masyarakat Menggunakan Metode Indeks Desa Zakat : (Studi Kasus Pada Kampung Zakat di Desa Iloheluma, Kecamatan Anggrek, Kabupaten Gorontalo Utara) - Datau, Raflian; Niswatin, Niswatin; Santoso, Ivan R. (Jurnal Maneksi (Management Ekonomi Dan Akuntansi), 2025)
This study aims to measure the level of welfare using the Zakat Vilage Index (IDZ) in the zakat village in iIloheluma Village, Anggrek District, North Gorontalo Regency. The research was conducted using quantitative method with Descriptive Quantitative approach. Data collection techniques were carried out by distributing questionnaires in the village and supported by observation and documentation. In the zakat village in Iloheluma Village, Anggrek District, North Gorontalo Regency, it was found that there was no calculation of indicators of effective distribution of zakat funds. so that this research can also provide recommendations for the village regarding the work program of the zakat village which will be developed later by the baznas. The results showed that the index value in Iloheluma Village, Anggrek District, North Gorontalo Regency has a zakat index value of 0.57, this shows that the results of this index are at 0.41 - 0.60, which in general the condition of Iloheluma Village is included in the good enough category and can be prioritized to be assisted through the zakat village work program. Keywords: Community Welfare Level: Calculation: and Zakat Village Index